calculus

posted by .

Find the derivative of the function.
G(y) =
(y − 1)3/
(y2 + 2y)7

  • calculus -

    Assuming you mean

    G(y) = (y-1)^3 / (y^2+2)^7

    then just use the quotient rule to get

    -(y-1)^2 (11y^2-14y-6) / (y^2+2)^8

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    i need to find when the function increases or decreases, this is the derivative of the function (10 − 3x)/(2 ¡î5 − x) but how do you solve the function when x is zero?
  2. Calculus

    find the derivative of the function. f(x) = − 1/7(x^-7-x^14)
  3. Calculus

    Use the Product Rule to find the derivative of the function. f(x) = (x^3 − 2x)(5x^2 + 2x)
  4. CALCULUS HELP

    Find the second derivative for the function 5x^3+60x^2-36x-41 and solve the equation F(X)=0 i got to the second derivative but what do we do next to be able to get one of these answers.. F(x) = 5x3+60x2−36x−41 1. derivative …
  5. Pre-Calculus

    Determine the derivative at the point (2,−43) on the curve given by f(x)=7−7x−9x^2. I know that the answer is -43, but I was wondering if it was just a coincidence that the derivative at the point (2,−43) is …
  6. Calculus

    Given f(x)=−2x^3 -3x + 1, the value of the derivative of the inverse function, f^−1(x) at x=−21 is (f^1)′(−21)= ?
  7. Calculus(easy)

    Suppose the derivative of a function f is f′(x)=(x−5)^3(x−3)^4(x+18)^8. Then the function f is increasing on the interval Can anyone please help me with this problem. It seems simple, but I just do not understand …
  8. math

    Use Part 1 of the Fundamental Theorem of Calculus to find the derivative of the function. g(x) = e^(3t^2) − 3t dt from 4 to x
  9. Calculus

    Suppose the derivative of a function f is f′(x)=(x−8)^7(x−1)^4(x+19)^8. Then the function f is increasing on the interval what?
  10. Calculus

    Hello I need help with this excersise of derivative of a inverse function. The excersise says: If f(x+2)=x^3+1 and g(x)=f(arctg x), find the derivative of the inverse function of g(x) and then calculate (g^-1 (9))'[the derivative of …

More Similar Questions